Cover Feature: Self‐Assembly of Chiro‐Optical Materials from Nonchiral Oligothiophene‐Porphyrin Derivatives and Random Coil Synthetic Peptides (ChemPlusChem 1/2023). Issue 1 (22nd November 2022) - Arja, Katriann; Selegård, Robert; Paloncýová, Markéta; Linares, Mathieu; Lindgren, Mikael; Norman, Patrick; Aili, Daniel; Nilsson, K. Peter R.
Abstract : The cover feature image illustrates the chiro‐optical properties and architectural arrangement of an optoelectronic material that are generated from self‐assembly between an anionic porphyrin and a cationic synthetic peptide. The material displays a helical structure and optical activity that are observed due to an induced chirality of the optoelectronic element upon interaction with the peptide. A similar phenomenon can also be observed for oligothiophene‐porphyrin hybrid materials when mixed with different peptides. The cover artwork was designed by Mathieu Linares. More information can be found in the Research Article by K. Arja, K. P. R. Nilsson and co‐workers .